Hubungan antara E-word of Mouth dengan Keputusan Pembelian Produk Online di Platform Shopee Perspektif pada Mahasiswa Fikom Unisba 2020 - Shafira Alifiya Putri; O.Hasbiansyah (Bandung Conference Series: Communication Management, 2024)
Abstract. The need for the internet has become commonplace in society, especially in Indonesia which is ranked first in the growth of internet users in the world. The Word of Mouth (WOM) phenomenon has shifted to Electronic Word of Mouth (eWOM), making it easier for people to share information about products or services online. Purchasing decisions are influenced by factors such as recommendations from peers, relevance of information, and credibility of information sources in eWOM. This research uses a quantitative approach and survey method through questionnaires to 78 respondents from Fikom Unisba 2020 students. The results of the research show that there is a relationship between Source of Influence, Relevance of Influence, Source Credibility, and E-Word of Mouth with the decision to purchase online products on the Shopee platform. Abstrak. Kebutuhan akan internet telah menjadi hal umum di masyarakat, terutama di Indonesia yang menjadi peringkat pertama dalam pertumbuhan pengguna internet di dunia. Fenomena Word of Mouth (WOM) telah bergeser menjadi Electronic Word of Mouth (eWOM), memudahkan orang untuk berbagi informasi tentang produk atau jasa secara online. Keputusan pembelian dipengaruhi oleh faktor-faktor seperti rekomendasi dari sesama, relevansi informasi, dan kredibilitas sumber informasi dalam eWOM. Penelitian ini menggunakan pendekatan kuantitatif dan metode survei melalui kuesioner kepada 78 responden Mahasiswa Fikom Unisba 2020. Hasil penelitian menunjukkan adanya hubungan antara Sumber Pengaruh, Relevansi Pengaruh, Kredibilitas Sumber, dan E-Word of Mouth dengan Keputusan Pembelian produk online di platform Shopee.